QUESTIONING STRATEGY AS PART OF EFL TEACHER KNOWLEDGE AND EXPERTISE - Valentyna Parashchuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The article addresses the problem of questioning as an important intellectual tool central to student learning and developing, as well as an integral part of an EFL teacher knowledge and expertise. An overview of research findings on the subject of classroom questioning has been made. A number of pedagogical implications concerning teacher questioning knowledge and skills relevant for the Ukrainian EFL classroom practices are outlined. The most popular cognitive scaffolds for questioning are discussed. The problem of priority of higher-cognitive questions or lower-cognitive questions in EFL instruction is seen as "one cannot be used without the other", with the teacher's choice depending upon the students' proficiency level, learning stages and classroom communication contexts. The concepts of "thinking routines" and "questioning sequences" are assumed to be efficient in the EFL teacher questioning behaviours. The author comes to the conclusion that TEFL programs at Ukrainian universities should offer a special course or academic modules to give prospective teachers theoretical insights and training to help them develop professional questioning skills.